2018
DOI: 10.1007/s11356-018-2043-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phytotoxins in different plant parts of Brassica napus and their influence on mung bean

Abstract: Plants in Brassica genus have been found to possess strong allelopathic potential. They may inhibit seed germination and emergence of subsequent crops following them in a rotation system. Series of laboratory and greenhouse experiments were conducted to determine the allelopathic impacts of Brassica napus L. against mung bean. We studied (1) the effects of aqueous extract (5%) of different plant parts (root, stem, leaf, flower, and whole plant) of B. napus, (2) the effects of leaf and flower extracts of B. nap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Therefore, corn should be sown more than 30 days after the ryegrass desiccation since there will be no phytotoxic influence and nitrogen immobilization effects after this period. The increase in inhibitory effect on germination and seedling growth by phytotoxic extract concentration is supported by the results of Mehmood et al (2018), who observed a similar allelopathic influence of Brassica napus against mung bean germination, in this case, after 21 days the inhibitory effect was reduced, because as the decomposition period changed the phytotoxic effect of the residues. Abbas et al (2009) observed a significant inhibition of different rice germination traits of rice due to the allelochemical influence of weed species.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, corn should be sown more than 30 days after the ryegrass desiccation since there will be no phytotoxic influence and nitrogen immobilization effects after this period. The increase in inhibitory effect on germination and seedling growth by phytotoxic extract concentration is supported by the results of Mehmood et al (2018), who observed a similar allelopathic influence of Brassica napus against mung bean germination, in this case, after 21 days the inhibitory effect was reduced, because as the decomposition period changed the phytotoxic effect of the residues. Abbas et al (2009) observed a significant inhibition of different rice germination traits of rice due to the allelochemical influence of weed species.…”
Section: Discussionsupporting
confidence: 61%
“…The green manure straw takes time to release the goosegrass-resistant potential substances and these substances may be produced with concomitant degradation, which gives rise to a peak in concentration, preceded by a gradual increase in goosegrass suppression potential and followed by a decrease. In a study exploring the effects of Brassica napus decomposition on the growth of mung beans, the decomposition period changed the phytotoxic effect of residues; more inhibitory effects were shown at 14 days of decomposition, whereas decomposition for 21 days reduced the inhibitory effect ( Mehmood et al., 2018 ). Puig et al.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the enormous number of phytotoxins and secondary metabolites produced in plants, these toxins' comprehensive identification and characterization have been studied in limited numbers. Mehmood et al [29] identified the different types of phenolic compounds such as quercitin, coumaric acid, ferulic acid, benzoic acid, cinnamic acid, caffeic acid, syringic acid, gallic acid, and chlorogenic acid in Brassica napus. Günthardt et al [30] conducted a comprehensive study and identified 1,586 plant phytotoxins, of which more than 60% belonged to the alkaloid and terpene classes.…”
Section: Identification and Classification Of Toxinsmentioning
confidence: 99%
“…In bioassay methods, depending on the plant species, the phytotoxin content of seeds, buds, leaves, roots, and even protoplasts can be targeted. However, the whole plant bioassay is also one of the most common methods [29,45].…”
Section: Detection Of Phytotoxinsmentioning
confidence: 99%
See 1 more Smart Citation